Percepción de las madres sobre la influencia de un hijo con discapacidad en la dinámica familiar en los pacientes del área de medicina física y rehabilitación del Hospital Belén de Trujillo - 2016 - Rojas Vega, Lizzeth (2017)
The present descriptive - explanatory study with mothers with children with disabilities patients of the Hospital Belén de Trujillo with the aim of knowing the perception of mothers about the influence of a child with disability in the family dynamics of children patients It was investigated in a systematic way and to the depth of the elements such as: roles, communication and norms; applying the interview as an instrument of data collection, performing an inductive-deductive analysis. The impact of a child with disability on family dynamics was pointed out, since the birth of a family member emphasizes the previously established ties, so effective communication is superficial and passive style, while the affective communication of the family has strengthened its ties, norms have been established according to the needs demanded, and in some situations it varies as is the case of roles, new roles are implemented in the family, the mother is the main caretaker of the child with disability, the other members support occasionally, the mother has sometimes been in need of stopping work to give greater care to that member, the brothers have come to feel relegated but also involved in the recovery process and the father also but less frequently since his role focuses on being the provider of resources.